Combining small extracellular vesicles with decellularized adipose tissue hydrogel for the construction of tissue-engineered adipose - Pengyu Hong; Shengmeng Yuan; Jian Yang; Zhiwei Cao; Xiangyun Sun; Ling Du; Dianri Wang; Jian Pan (Materials & Design, 2025)
Soft tissue defects from trauma or surgery remain challenging to repair due to poor regenerative capacity and fibrosis. Adipose tissue-derived small extracellular vesicles (sEVs) have emerged as promising agents for promoting adipogenesis and driving adipose tissue regeneration, offering significant potential for soft tissue defect repair. This study aimed to establish a novel cell-free strategy by integrating sEVs with decellularized adipose tissue hydrogel (sEVs@DAT) for adipose tissue regeneration and elucidate the underlying mechanisms. We identified that sEVs derived from both white adipose tissue (sEV-WAT) and brown adipose tissue (sEV-BAT) promoted mitochondrial metabolism and adipogenic differentiation of adipose-derived stem cells (ASCs) in vitro. Furthermore, the sEVs@DAT supported anti-inflammatory macrophage polarization, and significantly improved adipose tissue formation and vascularization in vivo. Transcriptomic profiling identified Senp2 as a key mRNA cargo enriched in both sEVs types. Functional studies revealed that knockdown of Senp2 impaired sEVs-induced mitochondrial activity, adipogenic gene expression, and ERK/AKT phosphorylation. These findings presented a cell-free therapeutic approach for adipose tissue engineering by integrating bioactive sEVs with a biocompatible scaffold, offering a translationally promising approach for soft tissue reconstruction over traditional cell-based therapies.